(3eUHGM GdTQjYI heaJGM GdMbjbIs - (3GdgGTej, GdbQTj, CHh YHO Gddg, GdUGOb, LYaQ GdUGOb Hf eMeO GdHGbQ, J (B148(3g`s ((3eMeO bdj CHh ChZdjs)
(3ChdgG (B:s
(3GdMeO ddg GdPj fhQ bdhH GdYGQajf(B... (3agPGcJHG eUHGM GdTQjYI heaJGM GdMbjbI(B...s
(3BNQgG (B:s
(3heYQaI BaGJgG hQaV TghGJgG eY QaV GdQjGSI (B... (3agh ef NGUI Gddg JYGdi hYHGOg GdebQHjf (B...(3JeJ GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B2(3, U(B126s
(3EjVGM Gdecfhf(B: (3L(B2(3, U(B492s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs